2015
DOI: 10.2147/ijgm.s81633
|View full text |Cite
|
Sign up to set email alerts
|

Management of rheumatoid arthritis in People's Republic of China – focus on tocilizumab and patient considerations

Abstract: The prevalence of rheumatoid arthritis (RA) is 0.19%–0.41% in Chinese population. RA exerts profound influence on health-related quality of life (HRQoL), which imposed huge burdens on patients physically, mentally, and economically. As a developing country, People’s Republic of China faces enormous challenges in management of RA. Conventional-synthesized disease-modifying antirheumatic drugs (csDMARDs) remain the most selective therapeutic options for RA in People’s Republic of China owing to their affordable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…This study showed that TCZ significantly improved patient condition by decreasing DAS28 score, CRP, RF, and CCP levels by more than half ( P <0.01). Our results are consistent with previous reports of TCZ remarkably improving RA patients at moderate and severe active stages [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…This study showed that TCZ significantly improved patient condition by decreasing DAS28 score, CRP, RF, and CCP levels by more than half ( P <0.01). Our results are consistent with previous reports of TCZ remarkably improving RA patients at moderate and severe active stages [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…RA exerts profound influence on health-related quality of life, which imposed huge burdens on patients physically, mentally, and economically [ 63 ]. The general effectiveness of typically prescribed medications for patients with RA, including NSAIDs and DMARDs, has been far from satisfactory [ 1 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is one of the most common chronic, in ammatory, autoimmune diseases with a prevalence of 0.5%-1% worldwide and 0.19%-0.4% in China [1,2]. Clinically, RA patients not only suffer from swelling and pain in both small joints (e.g., metacarpophalangeal) and large joints (e.g., ankle), but also may be affected by extra-articular manifestations such as rheumatoid vasculitis and interstitial lung disease [3].…”
Section: Introductionmentioning
confidence: 99%